The Business Ethics Index as a Leading Economic Indicator - Tsalikis, John (2011)
Theoretical justification for the Business Ethics Index (BEI) from the emerging economics of trust literature is discussed. The BEI results for 2007, 2008, and 2009 are presented. While the Personal/Past BEI component shows no significant difference from the previous years, the Vicarious/Past component shows a dramatic drop to levels previously never recorded. However, when it came to the perception of the future business ethical behavior, respondents were signifi- cantly more optimistic than in previous measurements. This finding was more than a little surprising given the depth of the economic crisis. A possible explanation is that consumers hopefully perceived the economic crisis as already abating and/or that at least the worst was over.
Keywords: consumer perceptions; Business Ethics; Economic indicators; business ethics index (BEI)